The Effectiveness of Distraction Play Intervention on Reducing Anxiety Levels in Children Undergoing Chemotherapy - Sistina, Norma; Allenidekania, Allenidekania; Gayatri, Dewi (Indonesian Journal of Global Health Research, 2024)
In addition to the unpleasant symptoms of the disease, invasive procedures, pain, and anxiety resulting from prolonged treatment and hospitalization n pediatic cancer. These can affect a child's physical, emotional and psychosocial functioning. Play is an important part of childhood and a basic need. Play therapy, through the playful nature of games, will create distraction from the pain, help children express emotions and adapt to the hospital environment. Objective: Therefore, it is necessary to identify non-pharmacological interventions to reduce anxiety in children undergoing chemotherapy.. Methodology: the literature Articles were searched using four databases: Pubmed, Scopus, Science Direct, and Sage journal which were published in 2018-2023. From 4 databases, 9317 articles were obtained and totaled final result are found 8 articles. They were reviewed and all were randomized controlled trial (RCT) studies which were assessed for risk of bias by using the Center for Evidence-Based Medicine (CEBM). Result: Distraction play interventions that can reduce anxiety levels in children undergoing chemotherapy include Art Therapy, Music Therapy, Virtual Reality, Muscle Relaxation, and Play Therapy. Conclusion: distraction play intervention can be applied in daily nursing practice to reduce anxiety in children undergoing chemotherapy treatment.